Mechanical behaviour of silver and copper nanoparticles when incorporated with Polylactic acid nanoparticles - Bobba, Sujith; Malyadri, T; Leman, Zulkiflle; Jyothula, Suresh K (Springer, 2024)
This current research work was performed on the integration of antimicrobial metal nanoparticles with thermoplastics and then to 3D print the obtained material. Mechanical properties such as tensile, compression and flexural were analyzed on the obtained specimens. The test specimens were developed of printed using fused deposition modelling method which involves material extrusion and the specimen parameters were taken based on the ASTM standards, Both the silver nanoparticles (AgNPs) and copper nanoparticles (CuNPs) were of 100 nm in size, 2% vol of AgNPs and CuNPs were added to Polylactic acid (PLA) granules, the nanoparticles were studied for concentration and scanning electron microscope (SEM) was utilized to investigate the composition of nanoparticles in Polylactic acid (PLA) granules.